2022
DOI: 10.3389/fpls.2022.858842
|View full text |Cite
|
Sign up to set email alerts
|

Bioprospecting Microbiome for Soil and Plant Health Management Amidst Huanglongbing Threat in Citrus: A Review

Abstract: Microorganisms have dynamic and complex interactions with their hosts. Diverse microbial communities residing near, on, and within the plants, called phytobiome, are an essential part of plant health and productivity. Exploiting citrus-associated microbiomes represents a scientific approach toward sustained and environment-friendly module of citrus production, though periodically exposed to several threats, with Huanglongbing (HLB) predominantly being most influential. Exploring the composition and function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 131 publications
(183 reference statements)
1
13
0
Order By: Relevance
“…The NMDS analysis showed clear separation (PERMANOVA p = 0.001) between healthy and infected (both symptomatic and asymptomatic) phyllosphere‐associated bacterial and fungal communities for both the tested varieties with different leaf ages (Figure 5). Thus, our results are per the previous studies that have reported the significant impact of HLB infection and disease severity on leaf microbiome (Srivastava et al, 2022; Wang, Stelinski, et al, 2017; Xu et al, 2018). This is because that HLB causes the imbalanced carbohydrate partitioning and deficiencies of micronutrients such as Fe, Mn, and Zn (Blaustein et al, 2017).…”
Section: Resultssupporting
confidence: 92%
“…The NMDS analysis showed clear separation (PERMANOVA p = 0.001) between healthy and infected (both symptomatic and asymptomatic) phyllosphere‐associated bacterial and fungal communities for both the tested varieties with different leaf ages (Figure 5). Thus, our results are per the previous studies that have reported the significant impact of HLB infection and disease severity on leaf microbiome (Srivastava et al, 2022; Wang, Stelinski, et al, 2017; Xu et al, 2018). This is because that HLB causes the imbalanced carbohydrate partitioning and deficiencies of micronutrients such as Fe, Mn, and Zn (Blaustein et al, 2017).…”
Section: Resultssupporting
confidence: 92%
“…Hence, there is a huge number of microbes still to be exploited, probably the count is larger than those already isolated (Bora and Bora, 2010;Bora et al, 2021b;Nasreen et al, 2020). With the recent developments in molecular fields, metagenomics is one such efficient approaches which enables to screen and identify all the bacteria, viruses, fungi, nucleic acid present in a particular habitat without the need of culturingthese microbes (Bora and Bora, 2008;Srivastava et al, 2022). In Rhizobium, the three genes: nod-nif-fix were identified which plays the complete role of Symbiotic Nitrogen Fixation in leguminous plants.…”
Section: Beneficial Microbesmentioning
confidence: 99%
“…SAR is induced by the pathogen infection which is mediated by salicylic acid and associated with the accumulation of pathogenesis-related (PR) proteins. While ISR is induced by some nonpathogenic microbes and is mediated by jasmonic acid or ethylene this is not associated with the accumulation of PR proteins (Boraet al, 2026;Srivastava et al, 2022). Microbe-or pathogen-associated molecular patterns (MAMPs/PAMPs) viz., flagellin is an essential structure that is conserved and recognized by receptor proteins in plants to induce the plant immune system.…”
Section: Increasing Usage Of Biopesticidesmentioning
confidence: 99%
“…Recent studies have documented that the changes in soil chemical properties, of which soil pH is the main factor, significantly contribute to GRP ( Zhang et al., 2020 ). The soil microbiota plays a key role in determining plant health and productivity by channeling various crucial soil functionalities, including mineralization and plant disease control ( Srivastava et al., 2022 ). Manipulating the soil microbiota is an effective way to alleviate GRP ( Lee et al., 2015 ; Dong et al., 2018 ; Seo et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%